PERANAN DUKUNGAN SUAMI TERHADAP KEMATANGAN KARIR DOSEN WANITA FKIP UNIVERSITAS SULTAN AGENG TIRTAYASA - Raudah Zaimah Dalimunthe; Sholih Sholih; Deasy Yunika Khairun (Jurnal Penelitian Bimbingan dan Konseling, 2019)
Female lecturers face various demands of the family and around their environment, the demands of work and the environment. Role one with other roles often contradicts later interferes with work, causing anxiety and stress. The research objective was to determine: (1) the level of career maturity of female lecturers, (2) husband's support, and (3) the contribution of husband's support to the career maturity of female lecturers. The technique in this study used correlation analysis and descriptive analysis. The research population of all female lecturers is 200 people. The sampling technique used purposive sampling with the following characteristics: (1) female lecturers who have husbands, (2) female lecturers who have and care for biological children, (3) female lecturers over 3 years. The results of this study were found: (1) overall data on the support of husbands of female lecturers at FKIP Untirta by 58.6% were in the moderate category, (2) overall data on career maturity of female lecturers at FKIP Untirta was 66.9% in the moderate, and (3) Husband's support contributes to career maturity by 34.1%, the rest is influenced by other factors of 65.9%Husband's Support, Career Maturity